2020
DOI: 10.1139/cjz-2019-0004
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for red fox (Vulpes vulpes) exploitation of anthropogenic food sources along an urbanization gradient using stable isotope analysis

Abstract: As urban areas expand, wildlife show adaptations to urban ecosystems. We tested two hypotheses for urban populations of red fox (Vulpes vulpes (Linnaeus, 1758)) in urban areas: the population pressure hypothesis, which posits that urban foxes make do with suboptimal habitat, and the urban island hypothesis, which presumes that urban areas provide high-quality habitat. We investigated habitat quality by investigating anthropogenic food in fox diets across a rural–urban gradient in Lancaster, Pennsylvania (USA).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…Sulfur compounds were the most significant findings in fox urine, accounting for 32% (17/ 53) of the endogenous scent compounds, and including the second most frequently found compound, 3-isopentenyl methyl sulfide (20), present in 14/15 foxes. Five sulfur compounds have only been found in foxes: 3-isopentenyl thiol (15), octanethiol (39), benzyl methyl sulfide 1.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Sulfur compounds were the most significant findings in fox urine, accounting for 32% (17/ 53) of the endogenous scent compounds, and including the second most frequently found compound, 3-isopentenyl methyl sulfide (20), present in 14/15 foxes. Five sulfur compounds have only been found in foxes: 3-isopentenyl thiol (15), octanethiol (39), benzyl methyl sulfide 1.…”
Section: Plos Onementioning
confidence: 99%
“…Increasing fox numbers have brought ecological, economic and health problems [1,8]. Foxes eat a wide variety of food including insects, reptiles and other wildlife, farm and domestic animals, various fruits and other plant materials and food scraps [2,[9][10][11][12][13][14][15]. Their ecological impact is profound in Australia, where they have spread throughout the continent since their introduction in the 19 th century [16].…”
Section: Introductionmentioning
confidence: 99%
“…The core direction of the development of agricultural machinery industry is the intelligence and mechanization of agricultural machinery, which is also the main direction of realizing agricultural modernization (Bukhtiyarova T.I. et al, 2021;Handler A.M. et al, 2020). Rotary tiller, as an important tillage machine, it is one of the important equipment to improve the tillage quality when it is used in field operation.…”
Section: Introductionmentioning
confidence: 99%
“…Food utilization is an important aspect in the study of mammalian carnivores since trophic resources dominate several aspects of their ecology (Macdonald, 1983;Bekoffetal., 1984;Silva et al, 2009;Faraz et al, 2019). Foxes are opportunistic animals known for having a diverse diet that allows them to survive in natural and human-altered habitats (O'Mahoney et al, 1999;Stuart & Stuart 2003;Dell'Arte et al, 2007;Savory et al, 2014;Handler et al, 2020). Common food items ingested by foxes usually include arthropods, rodents (e.g., mice, voles), birds and rabbits (Aryal et al, 2010;Dell'Arte et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the importance of each food item in the diet of foxes varies depending on various factors, including habitat type and regional prey availability (Dell'Arte et al, 2007;MacDonald, 1977). For instance, anthropogenic food items may represent a large fraction of the items ingested by foxes in urban and suburban areas (Aryal et al, 2010;Contesse et al, 2004;Newsome et al, 2010;Savory et al, 2014;Handler et al, 2020).…”
Section: Introductionmentioning
confidence: 99%